To Resist the Wave of Oblivion. The Continuing Multi-Volume Edition «The Great Victory» - A. V. Sereghin (Vestnik MGIMO-Universiteta)
The article, dedicated to multivolume continuing publication «The Great Victory» issued as a supplement to the «Vestnik MGIMO-Universiteta» magazine, deals with the most frequent examples of unscrupulous, or politically motivated, interpretation of the Second World War history. Further plans to continue the work on this publication are also expounded.